ANALISIS PENGARUH INFLASI, INVESTASI DAN PDRB TERHADAP TINGKAT PENGANGGURAN DI WILAYAH SULAWESI PERIODE 2010-2014 - Yanti, Nur Fitri (Katalogis, 2017)
This research was conducted in Sulawesi region, It aims at finding out: 1) The simultaneous and partial influence of inflation, invesment, and PDRB on the unemployment rate in Sulawesi. 2) The partial influence of inflation on the unemployment rate in Sulawesi. 3) The partial influence of Invesment on the unemployment rate in Sulawesi. 4) The partial Influence on the unemployment rate in Sulawesi. Panel data regression was used to analyze the data. The result show that first, the inflation, invesment, and PDRB simultaneously gives significant influence on the unemployment rate in Sulawesi in the period of 2010-2014. Second, the inflation gives insignificant negative influence on the unemployment rate in Sulawesi in the period of 2010-2014. Third, the invesment gives insignificant positive influence on the unemployment rate in Sulawesi in the period of 2010-2014. Fourth, PDRB gives insignificant negative influence on the unemployment rate in Sulawesi in the period of 2010-2014.